Hepatoscopy and Extispicy in Graeco-Roman and Early Christian Texts - Lawrence, John Michael
Diss.; Order No. 7920292; sacrificial divination spread from Mesopotamia to Anatolia, thence to Etruscans; Diss Abstr 40 (1979-80) 1625-A.